The effectiveness of the multi-soil-layering system in reducing pollutant parameters of crumb rubber industrial wastewater - Primandari, Sri Rizki Putri; Mulianti, Mulianti; Sushanti, Gusni; Gabbasa, Mohamed; Ba-Abbad, Muneer M. (Teknomekanik, 2023)
Multi-soil-layering (MSL) is well-known as an emerging technology for wastewater treatment. However, limited studies have been conducted on the crumb rubber industry. Thus, this study aims to reduce the crumb rubber industrial wastewater using MSL system. Four models of MSL conducted it. They are (1) constructed by body size of gravel with a mixture of andosol soil and fine charcoal; (2) body size of gravel with a mixture of andosol soil, fine charcoal, sawdust, and iron particles; (3) tube size of gravel with a mixture of andosol soil and fine charcoal; and (4) tube size of gravel with a mixture of andosol soil, fine charcoal and sawdust. The construction models were installed in the variance of the box and each of them was flowed by the Hydraulic Loading Rate of wastewater. Aeration treatment is given to the maximum hydraulic loading rate. The result showed that MSL systems significantly minimize the crumb rubber industrial wastewater under requirements that cover Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Total Nitrogen (T-N) and Total ammonia (T-NH3). It also significantly neutralizes the power of Hydrogen (pH) up to 6. The highest reduction was obtained by the MSL 3 system (tube size of gravel with a mixture of andosol soil and fine charcoal). The aeration significantly decreased the BOD, COD, TSS, and ammonia from 85% to 99%. Although the aeration process enhanced the performance of MSL system, however, MSL without aeration successfully treated the wastewater to meet the required standard. This study provides new insight into the effectiveness of MSL system in reducing pollutant parameters of crum rubber industrial wastewater.